Impact of cash grants on multidimensional poverty in South Africa - Atika Pasha (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
South Africa is estimated to allocate approximately US 12 billion for the 2014/15 fiscal year for social grants (Bhorat and Cassim, 2014). With an extensive coverage and budget, it is one of the most progressive social security schemes among low and even middle income countries. It helps mitigate income poverty and inequality, and has been shown to have a positive effect on household socioeconomic outcomes such as health and education, employment and other demographic outcomes. However, no study has thus far examined the impact of these grants on the overall or associative deprivation across households. This paper uses the National Income Dynamics Survey (NIDS) to derive the Multidimensional Poverty Index (MPI) and Correlation Sensitive Poverty Index (CSPI) for South Africa, and then estimate the impact that social assistance grants have on both of these composite indices of poverty measurement. The results show that increases in the income from a cash grant, leads to lower multidimensional poverty level in households. Another meaningful result is that cash grants seem to have reduced the multidimensional inequality as well. Using an instrument and a fuzzy Regression Discontinuity Design (RDD) to account for the issue of endogeneity in child and old age grants respectively, health and standard of living are found to be the major channels through which these grants work in reducing multidimensional poverty and inequality.
Keywords: H55; I38; 330; Social Assistance Grants; Multidimensional Poverty Index (MPI); Correlation Sensitive Poverty Index (CSPI); National Income Dynamics Survey (NIDS)